Beta-Blocker Therapy in Older (≥75 Years) and Frail Patients with Heart Failure: A Systematic Review and Meta-Analysis - Nurhayani Fatimah; Wahyudi; Taufik Rizkian Asir (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Beta-blockers are a cornerstone of therapy for heart failure with reduced ejection fraction (HFrEF), but their efficacy and safety in the burgeoning population of very elderly and frail patients, particularly those with preserved ejection fraction (HFpEF), remain uncertain. This population is characterized by unique pathophysiological features, including altered pharmacokinetics, heightened inflammation, and autonomic dysregulation, which may modulate the treatment effect. Methods: We conducted a systematic review and meta-analysis following PRISMA guidelines. We searched MEDLINE, Embase, and CENTRAL for randomized controlled trials (RCTs) and observational studies published between 2015-2025 that evaluated beta-blockers versus placebo or standard care in patients aged ≥75 years or defined as frail with heart failure. The primary efficacy outcome was all-cause mortality. The primary safety outcome was treatment discontinuation due to adverse events. Results: Eight studies (three RCTs, five observational) involving 8,512 patients were included. In the overall population, beta-blocker therapy was associated with a reduction in all-cause mortality (Hazard Ratio: 0.88; 95% CI: 0.79−0.98), but with significant heterogeneity (I2=68%). Subgroup analysis revealed this benefit was confined to patients with HFrEF (HR: 0.72; 95% CI: 0.63−0.83), with no benefit observed in HFpEF (HR: 1.09; 95% CI: 0.95−1.25). In frail patients with HFpEF, a trend towards harm was noted (HR: 1.21; 95% CI: 0.98−1.49). Beta-blockers significantly increased treatment discontinuation (Odds Ratio: 2.15; 95% CI: 1.55−2.98), driven primarily by bradycardia. Conclusion: Beta-blocker therapy reduces mortality in elderly patients with HFrEF, consistent with findings in younger populations. However, in elderly and frail patients with HFpEF, beta-blockers offer no mortality benefit and may be associated with harm, likely due to a pathophysiological mismatch between the drug's mechanism and the disease state.